2005
DOI: 10.1161/circulationaha.104.513689
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Quantification of Global and Regional Left Ventricular Function From Real-Time Three-Dimensional Echocardiographic Images

Abstract: Background-Real-time 3D echocardiographic (RT3DE) data sets contain dynamic volumetric information on cardiac function. However, quantification of left ventricular (LV) function from 3D echocardiographic data is performed on cut-planes extracted from the 3D data sets and thus does not fully exploit the volumetric information. Accordingly, we developed a volumetric analysis technique aimed at quantification of global and regional LV function. Methods and Results-RT3DE images obtained in 30 patients (Philips 750… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 213 publications
(137 citation statements)
references
References 39 publications
10
126
0
1
Order By: Relevance
“…The determination of regional LV volumes by 3D TTE shows a good correlation with CMR data. 8,9 Thorstensen et al have shown in their study that wall motion score index by 3D TTE presents a significant correlation with the extent of delayed gadolinium enhancement by CMR. 10 3D speckle-tracking echocardiography 3D speckle-tracking echocardiography represents an innovative technique used for the quantitative estimation of LV volumes and function, and regional wall motility disturbances with superior accuracy and reproducibility.…”
Section: D and 3d Echocardiographymentioning
confidence: 93%
“…The determination of regional LV volumes by 3D TTE shows a good correlation with CMR data. 8,9 Thorstensen et al have shown in their study that wall motion score index by 3D TTE presents a significant correlation with the extent of delayed gadolinium enhancement by CMR. 10 3D speckle-tracking echocardiography 3D speckle-tracking echocardiography represents an innovative technique used for the quantitative estimation of LV volumes and function, and regional wall motility disturbances with superior accuracy and reproducibility.…”
Section: D and 3d Echocardiographymentioning
confidence: 93%
“…3D-echocardiography visualizes the whole LV, and it is superior to 2D-echocardiography in assessment of regional wall motion abnormalities (Corsi et al,2005). It also visualizes endocardial surface structure within a beating heart (Inoue et al,2006).…”
Section: Potential Of Real-time 3d-mcementioning
confidence: 99%
“…The recently validated RT3DE volumetric quantification of global and regional LV function 88 overcomes limitations of 2D echocardiography as it eliminates geometric assumptions, identifies the true LV apex and evaluates wall motion encompassing all planes 89 . Jenkins, et al 90 demonstrated the correlation of RT3DE to MRI with lower intra and inter observer variability, whilst comparing it to computed tomography, Sugeng, et al 91 have shown its superiority in LVEF and volume measurement.…”
Section: Newer Parameters and Applicationmentioning
confidence: 99%